Patrick Chamoiseau : recovering memory - McCusker, Maeve (Contemporary French and francophone cultures ;, 2007)
This timely new book skilfully examines the work of the acclaimed writer Patrick Chamoiseau. McCusker sets the author in context, providing a valuable contribution to memory studies by looking at literary representation of memory in Martinique, a society founded on slavery but now politically assimilated to the metropolitan centre, France.